Government Guarantees : Allocating and Valuing Risk in Privately Financed Infrastructure Projects - Irwin, Timothy C. (Washington, DC: World Bank, 2012)
Government guarantees can help persuade private investors to finance valuable new infrastructure. But because their costs are hard to estimate and usually do not show up in the government's accounts, governments can be tempted to grant too many guarantees. Drawing on a diverse range of disciplines, including finance, history, economics, and psychology, Government Guarantees : Allocating and Valuing Risk in Privately Financed Infrastructure Projects aims to help governments give guarantees only when they are justified. It reviews the history of government guarantees and identifies the cognitive and political obstacles to good decisions about guarantees. It then develops a framework for judging when governments should bear risk in an infrastructure project (seeking to make precise the oft-invoked principle that risks should be allocated to those best placed to manage them); explains how guarantees can be valued; and discusses how aspects of public-sector management can be modified to improve the likely quality of government decisions about guarantees.